PENGARUH PENGEMBANGAN KARIR , PELATIHAN KERJA, DAN MOTIVASI INTRINSIK TERHADAP KINERJA KARYAWAN PT. VERENA MULTI FINANCE - Ipan Hilmawan, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
Career development is very important for an organization, because career is a need that must be continuously developed in an employee so as to motivate employees to improve their performance. Career development includes any activity to prepare a person for a particular career path. A career plan that has been made by a worker must be accompanied by a realistic career goal. Career Development Has a Positive and Significant Effect on Employee Performance. This is evident in the T-Statistic value of 3.732 > 1.96 with an effect of 0.309 and P-Values ​​of 0.000 < 0.5, therefore the proposed hypothesis can be accepted. Intrinsic motivation is the driving force that arises from within an employee to work well in order to achieve higher performance (Herzberg in Gibson, 2009). Thus, an intrinsically driven employee will enjoy work that allows him to use his creativity and innovation, work with a high degree of autonomy and does not need to be closely monitored. The same conclusion is also generated from research conducted by Hayati (2012) and Juliani (2007) which states that intrinsic motivation has a significant positive effect on employee performance.